Addressing individual and organisational factors influencing middle managers' synthesising role in knowledge creation and diffusion - Alexandros Psychogios; Konstantinos Alexandris; Andra Onofrei (2008)
Based on the widespread theoretical argument that Middle Managers (MM) are essential in making Knowledge Management (KM) work, this paper seeks to address the individual and organisational factors influencing their synthesising role in knowledge creation and diffusion within modern organisations. Two hundred and forty-one middle-level Greek managers (N = 241) participated in the research and completed Floyd and Wooldridge's (1996) ten-item scale, which measures the synthesising and implementing dimensions of knowledge creation and diffusion. The results indicated that the majority of middle-level managers are far from being knowledge synthesisers. They are merely conduits, translating plans into action, monitoring and controlling activities to keep things on track. In other words, their role in knowledge creation and diffusion is completely internal, because they lived their lives within the functional corridors of an organisation's hierarchy. Further statistical analysis indicated that there were individual factors, such as educational level and age, as well as organisational ones such as the size, type (public/private) and the years of existence of an organisation, which affect their synthesising role and involvement in knowledge creation and diffusion.